Programa de gestión de residuos sólidos para fortalecer la cultura ambiental de la I.E. María Inmaculada, distrito de Requena, 2020 - Hidalgo Ahuanari, Iris Estefany (2021)
The general objective of this research was to propose a solid waste management program to strengthen the environmental culture of the I.E. María Inmaculada, Requena district, 2020; opting for a descriptive, propositional research and non-experimental cross-sectional design, for which a sample of 257 students from said institution has been taken, who were surveyed through a questionnaire that analyzes their perception of the variables evaluated ; managing to conclude that solid waste management is deficient (37%), this due to the fact that there is great difficulty in organizing the teachers and students of said institution, likewise, it has been identified that there is no established process to process the SR generated, because the institution does not have the necessary infrastructure to reuse the solid waste generated. At the same time, it is possible to determine that the environmental culture of the students is largely low (38%), this due to the fact that they lack environmental knowledge, so there is minimal interest in caring for the environment, as well as lack of participation in environmental activities or solid waste management. Based on the identified problem, a solid waste management program has been proposed through which it seeks to improve the management of waste produced in the institution, as well as to create habits and values linked to the conservation of the environment and sustainable care, in addition to applying an environmental approach in the student curriculum.